Existing Problems in the Use of Cashless Forms of Payment in Uzbekistan and Ways to Solve Them - Normamatov Ikhtiyar Bakhtiyarovich (Research Parks Publishers, 2022)
Ensuring the efficiency of the use of cashless payments in Uzbekistan is one of the necessary conditions for the development of cashless payments. Improving the practice of using cashless forms of payment will play an important role in solving the problem of insolvency in the economy, ensuring the continuity of production activities of companies, the development of export-import operations. This, in turn, necessitates the identification of current problems associated with the improvement of the practice of using of payment and the development of ways to solve them. The article identifies the problems associated with the effectiveness of the use of cashless forms of payment in our country and develops scientific proposals to address them.